Clinical features and risk factors of Klebsiella pneumoniae infection in premature infants: a retrospective cohort study - Xiaofen Wei; Jiahui Liang; Huan Zhang; Chenglan Yan; Xiangjun Lu; Yan Chen; Linlin Li (BMC Infectious Diseases)
Abstract Background With the continuous advancement of modern medical technology, the survival rate of premature infants has significantly increased. Klebsiella pneumoniae (K. pneumoniae) is one of the most common pathogens causing neonatal infections, particularly posing a serious risk to premature infants. This study aimed to analyze the clinical characteristics, antibiotic susceptibility profiles, and treatment outcomes of K. pneumoniae infections in these infants. Methods We retrospectively compared cases of K. pneumoniae infection in premature and term infants admitted in a tertiary hospital from January 2017 to December 2022 in China. Clinical and microbiological characteristics were evaluated. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS), with statistical significance defined as P < 0.05. Results We enrolled 166 premature infants and 68 term infants. In premature infants, fetal distress, patent ductus arteriosus, patent foramen ovale, enteritis, anemia, hypoproteinemia, bloodstream infections, abdominal infection, mechanical ventilation, nasogastric feeding, drainage tube, parenteral nutrition, and prior exposure to carbapenem antibiotics were identified as significant risk factors for K. pneumoniae infections in univariate analysis. Furthermore, septic shock, bloodstream infections, abdominal infections, indwelling catheters, drainage tubes, parenteral nutrition, and previous exposure to glycopeptide antibiotics were significantly correlated with mortality. Independent risk factors for K. pneumoniae infections in premature infants included fetal distress (OR: 3.702, [95% CI: 1.056–12.986], P = 0.041), enteritis (OR: 4.434, [95% CI: 1.066–18.451], P = 0.041), anemia (OR: 4.028, [95% CI: 1.550-10.466], P = 0.004), bloodstream infections (OR: 1.221, [95% CI: 0.061–1.802], P = 0.022), mechanical ventilation (OR: 4.974, [95% CI: 1.685–14.685], P = 0.004) and prior exposure to carbapenem antibiotic (OR: 14.738, [95% CI: 2.393–90.767], P = 0.004). Additionally, abdominal infections (OR: 8.598, [95% CI: 2.000-36.957], P = 0.004) and indwelling catheters (OR: 7.698, [95% CI: 0.998–59.370], P = 0.050) were positive predictors of mortality. Conclusion K. pneumoniae isolates exhibit a notable prevalence of infection, poor treatment outcomes, and elevated resistance in preterm neonates. These findings enhance our understanding of K. pneumoniae infections and their association with clinical outcomes among premature infants.